Pelatihan Kewirausahaan dalam Pemanfaatan Media Sosial untuk Pengembangan UMKM Roti Kacang di Desa Pante Cermin - Boulqiah, Sultan; Imellani, Selly Siti; Yurisma, Fera; Amalia, Fitri; Tamimi, Cut Putri; Hamidi, Hamidi (Medan Resource Center, 2025)
Entrepreneurship training in utilizing social media for the development of peanut bread UMKM in Pante Cermin Village has had a very positive impact. This program is designed to improve the skills of UMKM actors in using social media platforms such as Instagram, Facebook, WhatsApp Business, and YouTube as a means of promotion. The approach applied is Participatory Action Research (PAR), which includes the stages of observation, planning, implementation, and evaluation. The results of the training show that UMKM actors are able to improve their abilities in managing social media accounts, creating interesting content, and utilizing interactive features to expand market reach. Sales increases were recorded to increase by 30% after one month, 80% after three months, and reaching 150% after six months. The training evaluation showed a sustainable positive impact, with sales trends continuing to increase to 250% after six months. In addition, UMKM actors are also encouraged to innovate in creating product variations and improving packaging design, thereby increasing competitiveness in the market.